Sodium-glucose co-transporter2 expression and inflammatory activity in diabetic atherosclerotic plaques: Effects of sodium-glucose co-transporter2 inhibitor treatment - Nunzia D'Onofrio; Celestino Sardu; Maria Consiglia Trotta; Lucia Scisciola; Fabrizio Turriziani; Franca Ferraraccio; Iacopo Panarese; Lella Petrella; Mara Fanelli; Piero Modugno; Massimo Massetti; Ludovica Vittoria Marfella; et al. (Elsevier, 2021)
Objective: We evaluated sodium-glucose co-transporter2 (SGLT2) expression and the effect of SGLT2 inhibitor (SGLT2i) therapies on carotid plaques of asymptomatic diabetic and non-diabetic patients. Methods: Plaques were obtained from 296 non-diabetic patients and 227 patients with type 2 diabetes undergoing carotid endarterectomy. 97 patients with type 2 diabetes were treated with SGLT2 inhibitors for 16 ± 4 months before endarterectomy. After propensity score matching analysis, patients with type 2 diabetes were categorized without (n = 87) and with SGLT2i therapy (n = 87). To investigate SGLT2 expression levels' effects on major adverse endpoints (MACE = stroke, transient ischemic attack, myocardial infarction, and death), we evaluated MACE outcomes at a 2-year follow-up. Results: Compared to plaques from patients without diabetes, plaques from patients with diabetes had higher SGLT2 expression, inflammation, and oxidative stress, along with lower SIRT6 expression and collagen content. Compared with plaques from patients with diabetes, SGLT2i-treated patients with type 2 diabetes presented increased SIRT6 expression and collagen content and lowered inflammation and ion and oxidative stress, thus indicating a more stable plaque phenotype. These results supported in vitro observations on human aorta endothelial cells (EC) (TeloHAEC-cells). Indeed, EC treated with high glucose (25 mM) in the presence of SGLT2i (100 nM canagliflozin) presented higher SIRT6 expression and decreased mRNA and protein SGLT2 levels, nuclear factor-kappa B (NF-B(NF-κB), and matrix metallopeptidase 9 (MMP-9) expression compared to cells treated only with high glucose. After two years following endarterectomy, a multivariable Cox regression analysis showed significantly higher 2-year overall survival from MACE in patients without diabetes (P < 0.01). Among patient with diabetes, the current SGLT2i users presented a significantly lower rate of MACE through 2 years compared to non-SGLT2i users (P < 0.05). Conclusions: These findings unveil a critical involvement of the SGLT2/SIRT6 pathway in the inflammatory process of diabetic atherosclerotic lesions and suggest its possible favorable modulation by SGLT2i.